MENINGKATKAN PARTISIPASI MAHASISWA TERHADAP PEMBERDAYAAN MASYARAKAT MELALUI PENDIDIKAN TINGGI ISLAM DI MASA 5.0 - Siti Suharni Simamora, M. Baihaqi, Leli Purnama, Indah Fitria Rahma, Mahsuratun Nisa (JURNAL BIMA, 2024)
Community Service, Al-Washliyah Tarbiyah College of Science, Binjai City is one of the implications of the Tri Dharma of Higher Education, namely Community Service. It is hoped that PKM for students can be a new learning experience to increase knowledge, abilities and awareness of social life. For the community, the presence of students is expected to provide motivation and innovation in the field of development. Therefore, students must be able to act as a bridge or (communication) in the development and application process (IPTEK).